Exploration of Specific Fluoroquinolone Interaction with SARS-CoV-2 Main Protease (Mpro) to Battle COVID-19: DFT, Molecular Docking, ADME and Cardiotoxicity Studies - Khan, Muhammad Asim; Mutahir, Sadaf; Tariq, Muhammad Atif; Almehizia, Abdulrahman A. (Molecules, 2024)
Herein, the pharmacokinetic profiles, binding interactions, and molecular properties of fluoroquinolone derivatives as prospective antiviral drugs are examined using a combination of docking, ADME, and DFT simulations. The effectiveness of the ligands is compared with the clinically tested and FDA-authorized medicine remdesivir. The findings demonstrated encouraging binding energies, indicating possible inhibitory effectiveness against SARS-CoV-2 Mpro. The fluoroquinolone derivatives also exhibit promising ADME characteristics, although compounds 5, 6, 9, 12–20 possess poor values, suggesting that oral administration may be possible. The potential of the selected compounds as SARS-CoV-2 Mpro inhibitors is thoroughly understood because of the integrated analysis of DFT, with compound 11 demonstrating the highest energy gap of 0.2604 eV of, docking with viral targets with docking scores of −7.9 to −5.9 kcal/mol, with compound 18 demonstrating the highest docking score, which is at the 13th position in energy difference in the DFT data. Their favorable electrical properties, robust binding interactions with viral targets, and attractive pharmacokinetic profiles boost their potential as prospective study subjects. These substances have the potential to be transformed into cutting-edge antiviral therapies that specifically target SARS-CoV-2 Mpro and related coronaviruses.